Strategi Dakwah dan Peran Jurnalis Islam pada Era Digital - Muhammad Yusuf; Muhammad Anshar (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This article is entitled " The Dakwah Strategy and Role of Muslim Journalists in the Digital Era", with the main points of analysis being first; what is the strategy for da'wah in the digital era and second: what is the role of Muslim journalists in developing da'wah. From these problems the author collected relevant data with the approach method used was a qualitative approach by describing the problem as a research priority. The research results show that journalism can be defined as the activities of journalists in searching, collecting and processing data so as to produce interesting news. These journalism activities are then continued by disseminating them to the public through print, electronic and digital media. journalism as the art of reporting, writing and disseminating information as well as a profession. Because the profession requires expertise and work according to one's expertise so that the person gets rewarded. The development of communication and information technology via the Internet has an impact on changes in the distribution of information. Distribution of information is getting faster and the public is also receiving it quickly. Therefore, the role of Muslim journalists in developing da'wah apart from functioning as a tool of information, education and entertainment, is also as a spiritual guide or developing the mission "amar ma'ruf nahi munkar".